Development of Digital Fashion Illustration Media Using Ibis Paint X Software to Improve The Competence of UNNES Fashion Students - Roudlotus Sholikhah; Widowati Widowati; Sita Nurmasitah (International Journal of Active Learning, 2023)
This study aims to develop digital media in the form of learning videos on the eyes of Digital Fashion Illustration with Ibis Paint X software so that it can be used in learning and can improve student competence. This research is development research which refers to the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) which includes: (1) the analysis phase, (2) the design phase, (3) the development phase, (4) implementation stage (trial), (5) evaluation stage. Digital media in the form of learning videos on the eyes of Digital Fashion Illustration with Ibis Paint X software that has been developed has been tested for eligibility by validators of media experts and material experts, as well as eligibility trials based on student responses of 40 students. The results of this study are in the form of digital media learning videos on the eyes of Digital Fashion Illustration with Ibis Paint X software. Based on the stages of media development that have been carried out, the final results of the eligibility assessment by media expert validators are 91.6% (very eligible), and the final eligibility assessment by the material expert validator is with a percentage of 97.5% (very eligible). At the implementation stage, the average result of the assessment based on the test student responses was 9.2 from the ideal score of 10 with a percentage of 92% (very positive). Thus, it can be said that digital video learning media for Digital Fashion Illustration with Ibis Paint X software is an eligible and practical medium to be used in learning Digital Fashion Illustration courses.